WORK ENGAGEMENT, EMOTIONAL INTELLIGENCE DAN FINANCIAL SATISFACTION DALAM MENINGKATKAN KINERJA PEGAWAI - Fitriani, Resa; Kusmayadi, Dedi (Jurnal Ekonomi Manajemen, 2024)
The aim of this research are to determine and analyze the influence of Work Engagement, Emotional Intelligence and Financial Satisfaction on the performance of employees within the Region XII Education Office of West Java Province. The research used was a survey method, data obtained directly through questionnaires to 341 respondents taken from the State Civil Apparatus (ASN) who worked under the Region XII Education Office of West Java Province. Sampling used simple random sampling and the analysis method used in this research was path analysis. ased on the results of the study, it is known that Work Engagement, Emotional Intelligence, Financial Satisfaction and the performance of employees in the Outreach of the Education Office of Region XII of West Java Province. The research used a survey method, the data obtained directly are included in the very good classification. Work Engagement, Emotional Intelligence, Financial Satisfaction partially affect the performance of employees in the Outreach of the Education Office of Region XII of West Java Province. Simultaneously Work Engagement, Emotional Intelligence and Financial Satisfaction affect the performance of employees in the Outreach of the Education Office of Region XII of West Java Province.